The effect of PhET simulation communication media on students' critical thinking skills on elementary school class V electrical circuit material - Handayani, Devi Fitri; Nurulpaik, Iik (International Conference on Education in Primary and Early Childhood, Marine, Computer Information, and Logistics, 2025)
The learning process is the most important stage because at this stage there is direct interaction between teachers, students, and learning materials, which aims to transfer knowledge, build skills, and develop attitudes and values. However, the learning process can be hampered due to the lack of learning media that attracts students' attention. The existence of additional interactive learning media makes learning more interesting and fun, so that students can be active in learning. This study uses a quasi-experimental method with a nonequivalent control group design involving an experimental class with PhET simulation learning media and a control class using conventional learning without physical tools. The population taken was 56 students from two different classes. The instruments used include a multiple-choice test based on critical thinking indicators, according to Robert Ennis. To determine the significance of the difference between the two groups, the data were analyzed using a T-test. The results showed that, compared to conventional learning media, PhET simulation learning media had a significant influence on students' critical thinking skills. This is shown by better posttest results for students in the experimental class compared to the control class. In addition, students in the experimental class are more active in group discussions and are able to identify and explain the concept of electrical circuits critically. The conclusion of this study is that PhET simulation media is effective in improving students' critical thinking skills in electrical circuit learning in elementary schools. This media can be an innovative alternative in improving the quality of science learning.
Keywords: learning media; PhET simulation; critical thinking skills